SKENARIO KEBIJAKAN PENGEMBANGAN PROVINSI SUMATERA SELATAN SEBAGAI LUMBUNG ENERGI NASIONAL - apriyanto, heri (Jurnal Sains dan Teknologi Indonesia, 2008)
The local government of South Sumatera Province and their people have desire to become a National Energy Stock (Lumbung Energi Nasional) is realistic. It is supported by the huge potential of energy resources and many kinds of nonrenewable energy (fossil) and renewable energy (nonfossil). Strategic position and basic infrastructure in this region support this plan. To realize this plan is needed direction and policy scenario as a reference in formulating the regional development program in order to support the realization of National Energy Stock. Based on the analysis of the existing strengths and opportunities, seven policies can be formulated to realize the National Energy Stock. Kata kunci : Lumbung energi nasional, Provinsi Sumatera Selatan,